Pengaruh Perputaran Piutang Dan Perputaran Modal Kerja Terhadap Rentabilitas Di Mediasi Margin Laba Bersih Pada Perusahaan Manufaktur Sektor Plastik Dan Kemasan - Anisa Putri Dz; Eka Nurmala Sari; Muis Fauzi Rambe (CERED Indonesia Institute, 2021)
This study uses a quantitative associative approach. The population in this study were all plastic and packaging companies listed on the Indonesia Stock Exchange from 2014 to 2018. The sample in this study used a purposive sampling technique, namely 6 companies. Data collection techniques in this study were carried out using documentation techniques. The data used in this research is quantitative data sourced from secondary data. The data analysis technique used is descriptive analysis and path analysis. The results of this study indicate that: (1) Accounts receivable turnover has a negative but insignificant effect on Profitability. (2) Turnover of working capital has a negative but insignificant effect on Profitability. (3) Accounts receivable turnover has a negative but insignificant effect on net profit margin. (4) Working Capital Turnover has a negative and significant effect on the net profit margin (5) The net profit margin has a significant effect on profitability. (6) net profit margin can be an intervening variable between accounts receivable turnover and profitability. (7 net profit margin cannot be an intervening variable between